2011
DOI: 10.1111/j.1600-9657.2011.00979.x
|View full text |Cite
|
Sign up to set email alerts
|

Pattern of mid-facial fractures in Tehran, Iran

Abstract: The main etiology of mid-facial fractures is automobile and motorcycle accidents. Protective measures were not observed in the majority of patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
23
0
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 18 publications
5
23
0
1
Order By: Relevance
“…The epidemiology about this trauma was similar to other studies; 21,22 72.3% were treated with an orbital reconstruction titanium mesh.…”
Section: Discussionsupporting
confidence: 83%
“…The epidemiology about this trauma was similar to other studies; 21,22 72.3% were treated with an orbital reconstruction titanium mesh.…”
Section: Discussionsupporting
confidence: 83%
“…This system was developed through direct observation, and incorporates what Le Fort described as "great lines of weakness" in the craniofacial skeleton. Through continued surgical experience, our understanding of the horizontal and vertical buttress systems of the face and their importance for successful reconstruction have become more nuanced (1)(2)(3). We also know that many facial fractures do not fit Le Fort's classification (1)(2)(3)(4)(5)(6)(7)(8).…”
mentioning
confidence: 99%
“…Much has changed since Le Fort's original descriptions; most craniofacial trauma now results from high-velocity motor vehicle collisions, often involving young males (2,3,17,19). This change in trauma mechanism and velocity may explain why many fractures observed today do not fit Le Fort's classification.…”
mentioning
confidence: 99%
“…The higher percentage of males in this regard is related to the observation that in most of the families, males extensively work outdoors in order to earn the livelihood for the family which in turn makes them more susceptible to involve in RTA and assault. Mohajerani and Asghari [18] analysed the pattern of maxillofacial fractures in north western Iran and state that road traffic accident was the commonest cause (40 %) and the age group of 21-30 comprised the biggest group (30 %). Adebayo et al [8] reported in their epidemiologic survey that the age range was from 3 years to 67 years (mean = 39.7) with a peak incidence in the 4th decade (n = 197, 36.3 %) with a male-female sex ratio of 3.7:1.…”
Section: Discussionmentioning
confidence: 99%